(untitled) (Per Musi, 2012)
This paper concerns with the notion of cadence, issue more related to harmony, but taken here under double aim: to reflect about the use of musical terminology (pointing out the lack of consensus among Brazilian authors), and to exemplify as the concept of cadence still remains active in post-tonal repertoire. Firstly, a historical review of the theme is presented, surveying how it is dealt in selected books, showing similar and conflicting points. Moreover, a classificatory approach to the effects of tension and relief inherent at chord progressions is suggested. Secondly, based on these understandings, the extension of the idea of cadential function to non-tonal repertoire is proposed, which is illustrated with conclusive progressions and tonicizing devices from musical works of the twentieth-century repertoire.